Nonobstructive urinary tract dilatation due to diabetes insipidus in a patient with craniopharyngioma - Ichiyanagi, N (Hinyokika kiyo. Acta urologica Japonica, 1995)
A 46-year-old man who had a history of hypogonadism, bilateral hydronephrosis and huge residual urine volume during the past ten years was admitted complaining of fever and flank pain. Polyuria which was more than 4 liters per day and inability of urine concentration suggested diabetes insipidus. Magnetic resonance imaging (MRI) demonstrated a tumor which was compatible with craniopharyngioma. Tumor resection and administration of desmopressin improved polyuria and urinary tract dilatation with marked reduction of residual urine volume from 400 ml to 20 ml